2007
DOI: 10.1080/00016480601002054
|View full text |Cite
|
Sign up to set email alerts
|

Chronic rhinosinusitis and psoriasis: do mutually exclusive systemic Th1 and Th2 disease patterns exist?

Abstract: Analysis of the data showed that occurrence of CRS rarely coincided with the occurrence of psoriasis and other such Th1 pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…One prior epidemiological study conducted on a retrospective electronic query of the medical records at Loyola University Hospital by Rashid et al. 9 further supported this understanding. From their analysis, they concluded that the occurrence of CRS rarely coincided with that of conditions with Th1 pathologies, including psoriasis.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…One prior epidemiological study conducted on a retrospective electronic query of the medical records at Loyola University Hospital by Rashid et al. 9 further supported this understanding. From their analysis, they concluded that the occurrence of CRS rarely coincided with that of conditions with Th1 pathologies, including psoriasis.…”
Section: Discussionmentioning
confidence: 79%
“…It is possible that previous studies were not conducted investigating this association because of the prior understanding that CRS is a T helper (Th) 2 pathology. As psoriasis is a Th1 pathology, 9 it would be unlikely that the two conditions would be comorbid, as disorders associated with a bias towards Th1 immunity have been proposed to skew comorbidities away from manifestations conventionally attributed to Th2‐mediated pathways 15 . On the other hand, as the presence of one Th1 pathology has been demonstrated to be strongly associated with the presence/occurrence of other comorbid Th1 pathologies, 16 it would be more likely that CRS would be associated with other Th1 pathologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a clear Th1 vs Th2 bias is not well demonstrated for other rheumatologic conditions, such as lupus and ankylosing spondylitis. A study by Rashid et al [6] suggested that autoimmune conditions may skew airway inflammatory disease away from Th2 pathways and would thus be associated with a decreased frequency of CRS. However, that study examined a limited sample of patients with autoimmune disorders (n = 1026 over a year period) and did not stratify CRS patients by NP status.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have examined the hypothesis that the presence of comorbid autoimmune mediated conditions may also impact the prevalence of CRS subtypes [6]. Specifically, disorders associated with a bias toward Th1 immunity (eg, multiple sclerosis, psoriasis, rheumatoid arthritis) have been proposed to skew comorbidities away from manifestations conventionally attributed to Th2-mediated pathways [7].…”
Section: Introductionmentioning
confidence: 99%